Análise de tensões residuais em tubulações soldadas - Costa, Antonia Daniele Souza Bruno (2007)
In the current industrial field in the country, we have sought, frequent and continuous, quality, economy and safety in production processes. One way to accomplish this is to avoid failures of equipment and components. Tensions remain a material that has ceased the external effort that gave rise to, are called residual stresses. Corrosive environments added to the residual stresses in the material the material can lead to mechanical failure by stress corrosion cracking or other processes that reduce the life of material.O objective of this study is to assess the levels of residual stresses induced by welding processes used in the pipes oil refineries, and compare these results with the microstructural variations of the material. We analyzed the levels of tension and the microstructures of the HAZ (heat affected zone by the heat) in ASTM A106 Gr B pipes of 2 "diameter welded with TIG Orbital (autogenous welding) without heat treatment and post-weld heat treatment. The welding was done with direct current and pulsed for two different energy levels. For each welding condition was applied heat treatment for stress relief (630 ° C for 96min) with diverse forms of cooling. We used the technique of X-ray diffraction as a tool to establish acceptance criteria for residual stresses in welded pipes. We used the technique of EBSD (Electron Backscattering Diffraction) for microstructural characterization. The material presented as received tensile stress along its outer surface. The soldier with various material parameters presented in compressive stress and tensile weld metal in the base metal. The post-weld heat treatments allowed the relief of residual stresses and a reduction in microhardness.